2018
DOI: 10.1155/2018/1395230
|View full text |Cite
|
Sign up to set email alerts
|

Adult Intussusception due to Gastrointestinal Stromal Tumor: A Rare Case Report, Comprehensive Literature Review, and Diagnostic Challenges in Low-Resource Countries

Abstract: We present a rare case of gastrogastric intussusception due to gastrointestinal stromal tumor (GIST) and the largest comprehensive literature review of published case reports on gastrointestinal (GI) intussusception due to GIST in the past three decades. We found that the common presenting symptoms were features of gastrointestinal obstruction and melena. We highlight the diagnostic challenges faced in low-resource countries. Our findings emphasize the importance of early clinical diagnosis in low-resource set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 46 publications
(27 reference statements)
1
37
0
3
Order By: Relevance
“…A review of 18 cases of intussusception secondary to GIST found that approximately 39% (7/18) of GISTs were within the small bowel. None of them had massive bleeding symptoms [26]. Thus, our case is the first reported and extremely rare manifestation presented as small bowel intussusception with massive bleeding from GIST.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A review of 18 cases of intussusception secondary to GIST found that approximately 39% (7/18) of GISTs were within the small bowel. None of them had massive bleeding symptoms [26]. Thus, our case is the first reported and extremely rare manifestation presented as small bowel intussusception with massive bleeding from GIST.…”
Section: Discussionmentioning
confidence: 85%
“…Small bowel intussusception from GIST in adults has been described in a few cases in the literature. Most of the reported adult cases manifested in abdominal pain and obstruction symptoms, with no symptoms of massive bleeding [26]. Cases of GIST with massive bleeding without intussusception are rarely described in the literature [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…GIST tumors are the most common cause of gastroduodenal intussusception. At 23 years, this patient is younger than the other previously reported cases of GISTs causing gastroduodenal intussusception (Mean age 64.5, median age 65 and range 29–95 years) [14] , [15] .…”
Section: Discussionmentioning
confidence: 60%
“…Ultrasound scan will show an echogenic fluid accumulation in the vagina that can extend to uterus. In low-resources setting like ours, however, imaging modalities may not be available [9,10].…”
Section: Discussionmentioning
confidence: 99%